A test of Wagner's hypothesis for the Ghanaian economy - John Gartchie Gatsi; Michael Owusu Appiah; Joseph Addo Gyan (Cogent Business & Management, 2019)
The economy of Ghana profiles a trajectory of increasing government expenditure at the backdrop of an inconsistent growth in real GDP. Thus, this study explores the causal relationship between real economic growth and real government expenditure in Ghana between the period 1960 to 2017. The Johansen (1991, 1995) cointegration method, the Autoregressive Distributed Lag bounds test approach and the Toda-Yamamoto non-Granger causality test are employed in this study. The findings are that the variables are cointegrated, and there is no Granger causality from real economic growth to real government expenditure. In effect, the causality shows that the Wagner's hypothesis does not hold in the case of the Ghanaian economy and that the Keynesian theoretical standpoint that public expenditure is an exogenous factor is not deflated in this case.
Keywords: 650; Wagner's hypothesis; economic growth; cointegration; Granger causality; autoregressive distributed lag model; Ghana